Serine Kinases as New Drug Targets for the Treatment of Type 2 Diabetes - Rondinone, Cristina M. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
Protein phosphorylation is the most common mechanism of protein function regulation. Protein kinases are key signaling enzymes that participate in the regulation of multiple cellular responses. Insulin regulates whole-body glucose homeostasis by modulating the activities of protein kinases in its target tissues: muscle, liver and fat. Defects in insulin's ability to modulate protein kinase activity lead to 'insulin resistance' or impaired insulin action. Recently, many serine kinases have been involved in the pathogenesis of obesity, metabolic syndrome and diabetes. These include the discovery of c-Jun N-terminal kinase (JNK), I kappa beta kinase (IKK), protein kinase C (PKC) theta, glycogen synthase kinase 3 (GSK3), S6 kinase-1 (S6K1) and 5'AMP-activated protein kinase (AMPK) as critical regulators of insulin action and glucose homeostasis. In this review, the mechanisms underlying kinases-induced insulin resistance, the impact of blocking this pathway in obesity and diabetes and the status of small molecule inhibitors will be discussed. It is expected that elucidation of the molecular mechanisms underlying regulation and specificity may prompt novel approaches for the pharmacological modulation of protein kinase activities involved in metabolic diseases. This review will give detail on recent discoveries and highlight emerging kinase targets that hold potential to reduce insulin resistance and normalize blood glucose.
Keywords: kinase inhibitors